2019
DOI: 10.1111/echo.14226
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial remodeling postseptal myectomy for severe obstructive hypertrophic cardiomyopathy: Analysis by two‐dimensional speckle‐tracking echocardiography

Abstract: Background: Septal myectomy relieves left ventricular outflow obstruction (LVOTO) and is associated with excellent long-term outcomes. LVOTO is associated with diastolic dysfunction and increased left atrial (LA) size. We sought to investigate the changes in LA volumes and function post myectomy and the association between these changes with clinical outcomes post myectomy.Methods: Sixty-six hypertrophic cardiomyopathy patients undergoing myectomy were retrospectively studied. Pre procedural and 6-to 18-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…Thus, the improvement in LV longitudinal strain in patients with HOCM after septal myectomy contributed to the increased LA reservoir function [ 23 , 24 ]. In contrast to our results, an echocardiographic investigation reported a reduction in reservoir strain after myectomy [ 25 ]. Compared to this study, their cohort differed substantially in the percentages of patients with hypertension (36%), coronary heart disease (11%), and a history of AF (26%).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the improvement in LV longitudinal strain in patients with HOCM after septal myectomy contributed to the increased LA reservoir function [ 23 , 24 ]. In contrast to our results, an echocardiographic investigation reported a reduction in reservoir strain after myectomy [ 25 ]. Compared to this study, their cohort differed substantially in the percentages of patients with hypertension (36%), coronary heart disease (11%), and a history of AF (26%).…”
Section: Discussioncontrasting
confidence: 99%
“…41 Both myectomy and alcohol ablation are associated with modest reduction in left atrial size over long-term follow-up. [42][43][44][45] Furthermore, in patients who develop advanced heart failure symptoms in the setting of end-stage nonobstructive HCM LA size is typically increased and ~50% of these patients have AF. [46][47][48] Increases in LA pressure and stretch are responsible for atrial dilation and fibrosis that in turn leads to shortening of the effective atrial refractory period and increased dispersion of depolarization.…”
Section: Pathophysiology Of Af Left Atrium Enlargementmentioning
confidence: 99%
“…41 Both myectomy and alcohol ablation are associated with modest reduction in left atrial size over long-term follow-up. 42–45 Furthermore, in patients who develop advanced heart failure symptoms in the setting of end-stage nonobstructive HCM LA size is typically increased and ~50% of these patients have AF. 46–48…”
Section: Pathophysiology Of Afmentioning
confidence: 99%
“…Their results corroborate previously published data: decreased left ventricular outflow tract gradient, left atrial diameter, left ventricular ejection fraction, and wall thickness after SM. [1][2][3] Postoperative cardiac magnetic resonance imaging, performed in 57 of 507 patients (8.9%), provides further insights. In particular, it showed that the degree of left ventricular late gadolinium enhancement (LGE) increased from 15.2% AE 9.6% to 18.6% (9.6%-31.2%) after SM (P ¼ .009).…”
mentioning
confidence: 99%